Psychological Hardiness and its relationship to psychological security among female's students at the University of Hail - Alslemi, Sarah Salman (Journal of Educational and Psychological Sciences, 2024)
This study aims to determine the relationship between psychological hardiness and psychological security among female student at the University of Hail. The study was followed by a correlational model, and the objectives of the study archived by using the following tools: the Mekhaimer Psychological Preparation Hardness Scale (2002) and the Abbabnah Preparation Psychological Security Scale (2021), sample of choices was selected from random (200) female students. The results of the study showed that there was an average level of psychological competence among the psychological students at the University of Hail, and the results showed an average level of psychological security among the female students at the University of Hail, and the existence of a positive, statistically significant correlation between psychological hardiness and the psychological security in the female students at the University of Hail.
Keywords: psychological security; psychological hardiness; female students at the University of Hail